A political discourse analysis of social memory, collective identity and nation-building in the Sunday Mail and the Standard of Zimbabwe between 1999 and 2013 - Santos, Phillip (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
Although much effort has been expended on studying many sites of social memory, little attention has been directed at the media's work of memory, especially in post-colonial Africa. The media's work of memory is important because of its social standing as a communicative and cultural institution, and because social memory is imbricated in processes of both collective identity formation and nation-building which partly shape patterns of economic distribution, recognition, and representation in society. It is in this context that this study shows how Zimbabwe's The Sunday Mail and The Standard newspapers used social memory to construct the country's national identity between 1999 and 2013 in the context of a socio-economic and political crisis for the country's poly-racial, and poly-ethno-linguistic communities. The study also explores how these newspapers worked as memory sites through their construction of Zimbabwe's national identity during the period under study. It achieves these tasks by analysing how these newspapers reported on such issues as Zimbabwe's colonial history, the country's narrative of decolonisation, the Gukurahundi narrative, the land reform process, elections and independence celebrations. The study takes a critical realist approach to qualitative research, and uses Fairclough and Fairclough's (2012) method of political discourse analysis as well as Aristotle's approach to rhetoric for a close reading of the sampled newspaper articles. It is informed by Nancy Fraser's Theory of Justice, Chantal Mouffe's Model of Agonistic Pluralism, and Jurgen Habermas's Discourse Ethics Theory. The study concludes that these two newspapers actively use social memory to construct versions of national identity for specific socio-political and economic ends. Editorials and opinions from The Sunday Mail, which construct Zimbabwean-ness in nativist terms represent the hegemonic appropriation of social memory to construct a sense of Zimbabwean nationhood. In contrast, The Standard uses social memory to construct Zimbabwean-ness in modernist terms with citizenship as the core organising principle of belonging. The political discourse analysis of The Sunday Mail's and The Standard's evocation of social memory shows that the two newspapers reflect the tension between indigenist and universalist imaginaries of belonging in Zimbabwe. But the newspapers' construction of belonging in Zimbabwe is informed by justice claims as seen from each of their political standpoints. As such, their respective definitions of Zimbabweans' justice claims in terms of their political standpoints, also propose how those justice claims should be addressed and who stands to benefit from them.
Keywords: Uncatalogued